Dose of information about laryngeal cancer with particular emphasis on laryngectomy - Gonet, Klara Elżbieta; Zaborek, Monika Karolina; Łyczba, Jakub; Borowik, Joanna Urszula; Przysucha, Anna (Journal of Education, Health and Sport, 2020)
Introduction and purpose: The laryngeal cancer is the most common cancer of head and neck and is associated with smoking. It is mainly squamous cell carcinoma. There are many methods to diagnosis this cancer. The most important method of the treatment is complicated operation – laryngectomy which is described in this article. There are presented diagnosis and staging of laryngeal cancer, the main types of laryngectomy, process, results and complications. And the end of this article will be mentioned about the loss of voice and of normal and efficient verbal communication as a negative consequence associated with this type of surgery that can have significant impacts on the quality of life. The purpose of this article is to familiarize readers with the topic of laryngectomy as the primary treatment for larynx cancer. Description of the state of knowledge: Studies show an increase in the incidence of this type of cancer. The main risk factors are smoking, drinking alcohol and exposure to heavy metals. Symptoms are really different and include hoarseness, sore throat, coughing and dysphagia. Depending on the location, the course of the cancer can be different. The main examinations are laryngoscopy, CT, MRI, USG and PET. The laryngectomy procedure as a main therapy must be radical as far as possible to the extent that the tumor can be resected within healthy tissue but the goal is to preserve the largest possible function of the organ. The most often complication is pharyngocutaneous fistula. Summary: The laryngectomy is the main method of therapy of the laryngeal cancer. it is a mutilating and often speech-depriving procedure but medicine has now many solutions for this kind of patients.